Effect of Solid-State Fermentation on Main Nutritional Components, Some Minerals, Condensed Tannin and Phenolic Compounds of Olive Leaves - Aydın Altop (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to investigate the effects of solid-state fermentation (SSF) on main nutritional components, some minerals, condensed tannin and phenolic compounds of olive leaves. Two groups were formed as a fermented (FOL, Aspergillus niger ATCC 52172) and non-fermented olive leaves (OL). Suitable environmental conditions (humidity, temperature and pH) before SSF were established and fermentation lasted on day 8. After fermentation, while the crude fiber, neutral detergent fibre (NDF) and acid detergent fibre (ADF) content of FOL compared to OL were decreased, its the crude protein, ether extract, ash and condensed tannin contents were increased. Some macro minerals (Ca, N, K, P, Mg) and micro minerals components (Fe, Mn, Zn, Cu, B) of FOL and OL were varied. Although oleuropein content of FOL was decreased, it’s catechin and hydroxytyrosol contents were increased by SSF. These results showed that A. niger ATCC 52172 strain could be suitable inoculant to improve the nutritional content of olive leaves.